Cleaning of Candidatus Liberibacter solanacearum in Bactericera cockerelli - Gamarra, H.; Panchi, N.; Naspud, J.; Vinueza, M.; Kreuze, Jan F. (2025)
This technical report demonstrates that using Lycium chinense (goji) as an alternative host allows for the progressive elimination of Candidatus Liberibacter solanacearum from Bactericera cockerelli colonies, establishing pathogen-free colonies after three generations. This advance represents a methodological milestone for transmission studies, epidemiological modeling, and the evaluation of integrated management strategies for the zebra chip-purple tip complex. The work aligns strongly with Crop Protection, Resilient Agrifood Systems, and Climate-smart Agriculture, providing a critical scientific foundation for regional phytosanitary research.